2006
DOI: 10.1128/jvi.00665-06
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Target Genes of Epstein-Barr Virus Nuclear Antigen 2

Abstract: Epstein-Barr virus (EBV) nuclear antigen 2 (EBNA-2) is a key determinant in the EBV-driven B-cell growth transformation process. By activating an array of viral and cellular target genes, EBNA-2 initiates a cascade of events which ultimately cause cell cycle entry and the proliferation of the infected B cell. In order to identify cellular target genes that respond to EBNA-2 in the absence of other viral factors, we have performed a comprehensive search for EBNA-2 target genes in two EBV-negative B-cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(156 citation statements)
references
References 69 publications
13
140
1
1
Order By: Relevance
“…EBNA2 is expressed first and strongly up-regulates MYC (48-50). MYC induces cyclin D2, and cyclin D2-enforced cell cycle entry likely induces CDKN2A p16 and p14 expression (48)(49)(50)(51)(52). CDKN2A p16 INK4A and p14 ARF are partially regulated by different promoters and have different first exons (exon 1α for p16 INK4A and 1β for p14 ARF ), but share exons 2 and 3 (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA2 is expressed first and strongly up-regulates MYC (48-50). MYC induces cyclin D2, and cyclin D2-enforced cell cycle entry likely induces CDKN2A p16 and p14 expression (48)(49)(50)(51)(52). CDKN2A p16 INK4A and p14 ARF are partially regulated by different promoters and have different first exons (exon 1α for p16 INK4A and 1β for p14 ARF ), but share exons 2 and 3 (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Since EBNA2 transactivates both LMP1 and LMP2A after initial infection of EBV, by stimulating the bi-directional viral latency C promoter and the LMP2A promoter [36], and EBNA2 also stimulates the expression of cellular genes including c-myc [36,83], it may be possible that EBNA2 is involved in stimulating the hTERT gene ( Figure 4). Being a nuclear antigen that does not bind to DNA directly, EBNA2 may transactivate target genes by hijacking the DNA-binding protein known as CBF1; it has been shown that after EBV infection, the viral EBNA2 binds to and activates CBF1 constitutively in the place of ICN [38].…”
Section: Regulation Of Telomerase Activity By the Ebv Proteinsmentioning
confidence: 99%
“…Because EBNA2 and EBNA3A regulation of transcription through RBPJ is essential for LCL growth, we investigated the overlap of EBNA3C and EBNA2 effects on transcript abundance in LCLs (41,51) and in BL cells (52). Notably, all significant EBNA2 effects on LCL RNAs are up-regulatory (41,51).…”
Section: Ebna3c-regulated Genes Overlap With Ebna2-and Ebna3a-regulatedmentioning
confidence: 99%
“…2). (ii) Several potentially important genes for LCL cell growth or survival changed with FDR < 0.05 significance or with <1.5-fold effect. KLHL6 HSPA1A ENO2 CST3 PON2 ALDOC RAB13 IFI27 CYP1B1 SLC2A3 P4HA2 SERPINA1 SOX9 LMNB1 TBC1D4 MAL DUSP2 MNDA CRIP1 HMGCS1 ARHGAP6 XCL1 LTA CCL22 CD24 CXCL12 ASCL1 LGALS8 CXCR4 FRMD4B TUBB2B S100A6 OAS3 C7orf68 TMEM45A EVC STAG3 NOD2 BNIP3L TMEM120A IL17RB TMEM107 AICDA C5orf32 CNN3 PFKFB4 TOX2 GPR133 LOC285628 MAFF GIMAP1 RAP1A FAM120A SCARB2 RRM2 TRIB1 ARHGAP25 AMMECR1 HIST1H4C EIF4G1 ATRX HIST1H1C LYN AKAP9 LHX2 BAT2D1 MTUS1 PSME4 QKI IGJ ZNF3 ANKMY2 IQGAP1 SFRS2IP ANKRD36 HIST1H2AC TPR GIMAP5 ANKRD12 BZW2 ARL5A ZNF281 CHST12 CCDC88A KLF13 CLEC4A YTHDF2 THRAP3 FAM46C AFF3 GIMAP7 BTNL9 DST CHD9 SGOL2 RIF1 KBTBD8 NIPBL Although EBNA2 has a much larger initial effect on MYC upregulation in LCLs, EBNA3C 1.3-fold up-regulation could be important at a specific point in cell cycle or under specific growth conditions, as has been described for the EBNA3C effect on EBV LMP1 expression in Latency III infected Raji BL cells (9,40,41). Also, TCL1A was EBNA3C up-regulated 1.7-fold, with FDR < 0.05.…”
Section: Ebna3cmentioning
confidence: 99%